Aerobic Exercise Preconception and During Pregnancy Enhances Oxidative Capacity in the Hindlimb Muscles of Mice Offspring. Issue 5 (May 2018) - Liu, Jenney; Lee, Icksoo; Feng, Han-Zhong; Galen, Sujay S.; Hüttemann, Philipp P.; Perkins, Guy A.; Jin, J.-P.; Hüttemann, Maik; Malek, Moh H.
Abstract : Abstract: Liu, J, Lee, I, Feng, H-Z, Galen, SS, Hüttemann, PP, Perkins, GA, Jin, J-P, Hüttemann, M, and Malek, MH. Aerobic exercise preconception and during pregnancy enhances oxidative capacity in the hindlimb muscles of mice offspring. J Strength Cond Res 32(5): 1391–1403, 2018—Little is known about the effect of maternal exercise on offspring skeletal muscle health. The purpose of this study, therefore, was to determine whether maternal exercise (preconception and during pregnancy) alters offspring skeletal muscle capillarity and mitochondrial biogenesis. We hypothesized that offspring from exercised dams would have higher capillarity and mitochondrial density in the hindlimb muscles compared with offspring from sedentary dams. Female mice in the exercise condition had access to a running wheel in their individual cage 30 days before mating and throughout pregnancy, whereas the sedentary group did not have access to the running wheel before mating and during pregnancy. Male offspring from both groups were killed when they were 2 months old, and their tissues were analyzed. The results indicated no significant ( p > 0.05) mean differences for capillarity density, capillarity-to-fiber ratio, or regulators of angiogenesis such as VEGF-A and TSP-1. Compared with offspring from sedentary dams, however, offspring from exercised dams had an increase in protein expression of myosin heavy chain type I (MHC I) (∼134%; p = 0.009), but no change in MHC II. For mitochondrial morphology, we found significant (all p -values ⩽ 0.0124) increases in mitochondrial volume density (∼55%) and length (∼18%) as well as mitochondria per unit area (∼19%). For mitochondrial enzymes, there were also significant (all p -values ⩽ 0.0058) increases in basal citrate synthase (∼79%) and cytochrome c oxidase activity (∼67%) in the nonoxidative muscle fibers as well as increases in basal (ATP) (∼52%). Last, there were also significant mean differences in protein expression for regulators (FIS1, Lon protease, and TFAM) of mitochondrial biogenesis. These findings suggest that maternal exercise before and during pregnancy enhances offspring skeletal muscle mitochondria functionality, but not capillarity.